Hydrophobicity-controllable nano silicon dioxide as well as preparation method and application thereof

By quantitatively controlling hydrophobic and hydrophilic groups on the surface of nano silica, the problem of unstable dispersion in the oil phase is solved, and the effect of stably suspending water-soluble polymer compounds in the oil phase is achieved, which enhances the dispersion performance and stability.

CN119306225APending Publication Date: 2025-01-14CHINA NAT PETROLEUM CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310860356.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The dispersion of nano silica in the oil phase is unstable and it is difficult to suspend water-soluble polymer compounds. The existing modification methods cannot effectively solve their stability and dispersion problems in the oil phase.

Method used

By quantitatively controlling the number of hydrophobic and hydrophilic groups on the surface of nanosilicon dioxide, the grafted hydrophobic modifier and hydrophilic modifier are used to regulate the hydrophilic and hydrophobic balance of their surfaces so that they can be used in oil Water-soluble polymer compounds are dispersed and suspended in the phase.

Benefits of technology

The dispersion performance and stability of nanosilicon dioxide in the oil phase is improved, agglomeration is avoided, its ability to suspend polymer compounds is enhanced, and the stability time of the system is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of oilfield chemistry, in particular to hydrophobicity-controllable nano silicon dioxide and preparation and application thereof.The hydrophobicity-controllable nano silicon dioxide is prepared according to the following steps that firstly, the required amount of nano silicon dioxide and a solvent are added into a first reactor, and ultrasonic dispersion is conducted; 2, adding a required amount of a solvent, a hydrophobic modifier and a hydrophilic modifier into a second reactor, sealing the second reactor, and stirring at normal temperature to obtain a modifier mixed solution; and 3, adding hydrochloric acid into the first reactor at the required temperature to adjust the pH value, adding the modifier mixed solution into the first reactor, stirring and reacting for 10-15 hours, and centrifuging, washing, drying and grinding the reaction product to obtain the hydrophobic controllable nano silicon dioxide. The number of hydrophilic groups and hydrophobic groups is quantitatively controlled on the surface of the nano silicon dioxide, so that the nano silicon dioxide can be dispersed in an oil phase and can suspend a high-molecular compound, and meanwhile, the dispersing performance of the nano silicon dioxide is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry and relates to nano silicon dioxide with controllable hydrophobicity and preparation and application thereof. Background Art

[0002] With the exploration and development of unconventional oil and gas reservoirs, higher requirements are put forward for fracturing fluids. In order to meet the requirements of pumping, continuous mixing, and ready-to-use, thickeners are currently prepared in the form of liquid guar gum, oil-based suspension emulsions, etc. This method is to pre-treat the powdered thickener so that its long molecular chain can exist in an unfolded form and can be quickly dispersed after entering the water system. Since the thickener is a hydrophilic polymer compound, an oil-based phase is used during pretreatment. In order to increase the stability of the thickener in the oil-based phase, clay is added to the system as a suspending agent, and the high surface area of ​​the clay increases the suspension capacity of the thickener. However, the introduction of clay increases solid impurities, increases damage to the reservoir, and reduces the effect of fracturing to increase production.

[0003] Nano-silica particles are ideal nanomaterials for oilfield applications because of their low price and environmental friendliness. However, nano-silica has a very high specific surface area and can play the role of suspension of clay. However, nano-silica exhibits a strong surface effect, which makes nano-silica easy to agglomerate after dispersion, which is not conducive to the stable dispersion of nanoparticles in the suspension system. Moreover, there are a large number of hydrophilic groups on the surface of silica, which cannot be dispersed in the oil phase. Therefore, the study of the stable dispersibility of nano-silica in oily systems is an unavoidable issue. At present, the stability of nanoparticles is mainly enhanced from two aspects: charge stability and spatial stability. Based on these two mechanisms, physical-chemical means are used to modify the surface of nano-silica particles to reduce their hydrophilic properties, thereby achieving the purpose of improving their stable dispersibility. Among them, the most studied nano-silica modification method is wet modification, which uses stearic acid, oleic acid, silane coupling agent, etc. to graft silica.

[0004] The Chinese patent document with publication number CN113234335A discloses a surface modification method of nano-silicon dioxide, which modifies nano-silicon dioxide particles by using a tridecafluorooctyl triethoxysilane coupling agent. The coupling agent replaces the hydroxyl groups on the surface of the nano-silicon dioxide to improve the dispersibility, compatibility and stability of the nano-silicon dioxide in an organic dispersant or matrix. Silane coupling agent is the most representative coupling agent. It is most effective for inorganic particles with hydroxyl groups on the surface and is very suitable for surface modification of nano-silicon dioxide. The conventionally used KH series silane coupling agent contains a hydrophilic group at the tail end, and the number of hydrophilic groups of the modified silica is still large, and its dispersibility in oil is poor. In order to improve the hydrophobicity and dispersibility of nano silicon dioxide, the Chinese patent literature that publication number is CN111040472A discloses a kind of modified nano silicon dioxide and modification method thereof, anticorrosive coating and coating, it is modified with hexamethyldisilazane and hexamethyldisiloxane to nano silicon dioxide, and abandoned the three-step method of traditional " modification-separation-drying ", nano silicon dioxide solution and silane modifier are carried out the method for " respectively dosing, primary reaction ", the modified nano silicon dioxide obtained has excellent dispersibility and hydrophobicity, can be well dispersed in multiple organic solvents.But, in the field of petroleum, except organic solvent, also contain water-soluble macromolecular compound, only utilize silane coupling agent to carry out hydrophobic modification to nano silicon dioxide and can not well suspend these water-soluble macromolecular compounds.So in order to utilize nano silicon dioxide to suspend water-soluble macromolecular compound in oil phase, the hydrophobic group on nano silicon dioxide surface and the balance of hydrophilic group should be considered. Summary of the invention

[0005] The present invention provides a nano-silicon dioxide with controllable hydrophobicity, which overcomes the shortcomings of the above-mentioned prior art and can effectively improve the ability of the nano-silicon dioxide to suspend aqueous polymer compounds in an oil phase.

[0006] One of the technical solutions of the present invention is achieved by the following measures: a hydrophobicity controllable nano-silicon dioxide is prepared by the following steps: The first step is to add the required amount of nano-silicon dioxide and solvent into the first reactor and disperse them by ultrasonic; The second step is to add the required amount of solvent, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH to 4.5 to 5, add the modifier mixture to the first reactor, stir the reaction for 10 to 15 hours, and centrifuge, wash, dry and grind the reaction product to obtain nano-silica with controllable hydrophobicity.

[0007] The following are further optimizations and / or improvements to the above technical solutions: The solvents in the first and second steps are both cyclohexane. In the first step, the mass ratio of nano-silica to cyclohexane is 3 to 5:8 to 9. In the second step, the mass ratio of the total mass of the hydrophobic modifier and the hydrophilic modifier to cyclohexane is 2 to 8:20 to 30.

[0008] The hydrophobic modifier is trimethoxy(pentyl)silane or trimethoxy(hexyl)silane.

[0009] The hydrophilic modifier is 1-amino-5-(trimethoxysilyl)pentane-2-ol or 1-amino-6-(trimethoxysilyl)hexane-2-ol.

[0010] The mass ratio of the hydrophobic modifier to the hydrophilic modifier is 3 to 6:1.

[0011] The mass ratio of the hydrophobic modifier, the hydrophilic modifier and the nano-silica is 3 to 6:1:30 to 60.

[0012] In the third step, the particle size of the hydrophobicity-controllable nano-silicon dioxide obtained after grinding is 30 nm to 50 nm.

[0013] In the first step above, nano silicon dioxide is prepared by a hydrolysis precipitation method.

[0014] In the third step, 1 mol / L hydrochloric acid was added to the first reactor at 40° C. to 60° C. to adjust the pH.

[0015] The second technical solution of the present invention is achieved by the following measures: A method for preparing nano-silicon dioxide with controllable hydrophobicity comprises the following steps: The first step is to add the required amount of nano-silicon dioxide and solvent into the first reactor and disperse them by ultrasonic; The second step is to add the required amount of solvent, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH to 4.5 to 5, add the modifier mixture to the first reactor, stir the reaction for 10 to 15 hours, and centrifuge, wash, dry and grind the reaction product to obtain nano-silica with controllable hydrophobicity.

[0016] The third technical solution of the present invention is achieved through the following measures: application of nano-silicon dioxide with controllable hydrophobicity in fracturing fluid and drilling fluid.

[0017] The present invention quantitatively controls the number of hydrophilic groups and hydrophobic groups on the surface of nano-silicon dioxide by grafting hydrophobic modifiers and hydrophilic modifiers, and reduces the hydrophilicity of the surface of nano-silicon dioxide to the greatest extent possible, so that it can be dispersed in the oil phase; and retains a small part of the hydrophilic groups, so that it can react with the polymer compound containing a large number of hydrophilic groups to suspend the polymer compound. The coexistence of hydrophilic and hydrophobic groups on the surface of nano-silicon dioxide also avoids copolymerization caused by a single hydrophilic group and hydrophobic association caused by a single hydrophobic group, thereby increasing the dispersibility of nano-silicon dioxide. DETAILED DESCRIPTION

[0018] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art; the percentages in the present invention are all mass percentages unless otherwise specified.

[0019] The present invention will be further described below in conjunction with embodiments: Example 1: The hydrophobicity controllable nano-silicon dioxide is prepared according to the following steps: The first step is to add the required amount of nano-silicon dioxide and solvent into the first reactor and disperse them by ultrasonic; The second step is to add the required amount of solvent, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH to 4.5 to 5, add the modifier mixture to the first reactor, stir the reaction for 10 to 15 hours, and centrifuge, wash, dry and grind the reaction product to obtain nano-silica with controllable hydrophobicity.

[0020] Example 2: As an optimization of the above example, the solvents in the first and second steps are both cyclohexane, in the first step, the mass ratio of nano-silica to cyclohexane is 3 to 5:8 to 9, and in the second step, the mass ratio of the total mass of the hydrophobic modifier and the hydrophilic modifier to cyclohexane is 2 to 8:20 to 30. In the third step of the present invention, the reaction product is washed with anhydrous ethanol, and the drying conditions after washing are 105° C. for 6 h to 10 h.

[0021] Example 3: As an optimization of the above example, the hydrophobic modifier is trimethoxy (pentyl) silane or trimethoxy (hexyl) silane.

[0022] Example 4: As an optimization of the above example, the hydrophilic modifier is 1-amino-5-(trimethoxysilyl)pentane-2-ol or 1-amino-6-(trimethoxysilyl)hexane-2-ol.

[0023] The two silane coupling agents selected as the hydrophobic modifier and the hydrophilic modifier in the present invention have large steric hindrance of the -R group grafted on the surface of the nano-silica particles, and the water-soluble polymer compound in the fracturing fluid and the nano-silica particles have hydrophobic affinity and electrostatic repulsion. When the polymer compound and the nano-silica are in contact, the number of segments of the polymer long chain in the polymer compound attached to the surface of the nano-silica is the least. Under this mechanism, the polymer chain can be better dispersed in the organic solvent, and bridge between the nano-silica particles to form a 3D network.

[0024] Example 5: As an optimization of the above example, the mass ratio of the hydrophobic modifier to the hydrophilic modifier is 3 to 6:1.

[0025] Example 6: As an optimization of the above example, the mass ratio of the hydrophobic modifier, the hydrophilic modifier and the nano-silica is 3 to 6:1:30 to 60.

[0026] Example 7: As an optimization of the above example, in the third step, the particle size of the hydrophobicity-controllable nano-silica obtained after grinding is 30 nm to 50 nm.

[0027] Example 8: As an optimization of the above example, in the first step, nano silicon dioxide is prepared by a hydrolysis precipitation method.

[0028] The hydrolysis precipitation method, also known as the in-situ polymerization method, includes the manufacture and dispersion of nano silicon dioxide at the same time, avoids the drying, storage, transportation and dispersion of nano particles, reduces the aggregation of nano silicon dioxide particles, and the nano silicon dioxide obtained by the hydrolysis precipitation method in the present invention contains a large amount of hydroxyl groups on its surface, which makes it hydrophilic and cannot be stably suspended in the oil phase. The silane coupling agent of the hydrophobic modifier consumes a large amount of hydroxyl groups on the surface of the nano silicon dioxide to increase the hydrophobicity of the silicon dioxide. However, in the field of petroleum, conventionally used are water-soluble polymer compounds, which are dispersed in the oil phase and contain a large amount of hydrophilic groups. The suspending agent can act on these hydrophilic groups. Therefore, in order to utilize nano silicon dioxide to suspend water-soluble polymer compounds in the oil phase, the affinity and repellency of the nano silicon dioxide surface must be controlled in a balance, that is, the hydrophobic modifier: hydrophilic modifier: nano silicon dioxide mass ratio is controlled to: 3 to 6:1:30 to 60.

[0029] Example 9: As an optimization of the above example, in the third step, 1 mol / L hydrochloric acid is added to the first reactor at 40°C to 60°C to adjust the pH.

[0030] Example 10: Application of the hydrophobicity-controllable nano-silica in fracturing fluid and drilling fluid.

[0031] The surface of the nano-silicon dioxide obtained by the hydrolysis method in the present invention contains a large number of hydroxyl groups, is hydrophilic, and cannot be stably suspended in the oil phase. A large number of hydroxyl groups on the surface of the nano-silicon dioxide are replaced by a silane coupling agent to increase the hydrophobicity of the silicon dioxide. However, in the field of oil reservoir development, a large number of water-soluble polymer compounds are conventionally used to disperse these polymer compounds containing a large number of hydrophilic groups in the oil phase, and a suspending agent is required to act with these hydrophilic groups. Therefore, in order to use nano-silicon dioxide to suspend water-soluble polymer compounds in the oil phase, the affinity and hydrophobicity of the surface of the nano-silicon dioxide must be controlled in a balance. The hydrophobic modifier trimethoxy (pentyl) silane or trimethoxy (hexyl) silane used in the present invention has an alkyl tail end and is completely hydrophobic; the hydrophilic modifier 1-amino-5-(trimethoxysilyl) pentane-2-ol or 1-amino-6-(trimethoxysilyl) hexane-2-ol has an amino group and a hydroxyl group at the tail end. By regulating the number of hydrophilic groups and hydrophobic groups, the hydrophilicity and hydrophobicity of the modified nano-silica surface are balanced. The proportion of the modifier containing hydrophobic groups added in the grafting reaction in the third step of the preparation method of the present invention is high, while the proportion of the modifier containing hydrophilic groups is low, so that the hydrophilicity of the surface of the nano-silica is reduced to the greatest extent possible, so that it can be dispersed in the oil phase; and a small part of the hydrophilic groups is retained, so that it can react with the polymer compound containing a large number of hydrophilic groups to suspend the polymer compound. The coexistence of hydrophilic and hydrophobic groups on the surface of the nano-silica also avoids copolymerization caused by a single hydrophilic group and hydrophobic association caused by a single hydrophobic group, thereby increasing the dispersibility of the nano-silica. Therefore, the hydrophobicity-controllable nano-silica of the present invention enables the modified nano-silica to be dispersed in the oil phase and to react with the polymer compound containing a hydrophilic group, which can help the polymer compound to be suspended in the oil phase.

[0032] The present invention quantitatively controls the number of hydrophilic groups and hydrophobic groups on the surface of nano-silicon dioxide by grafting a hydrophobic modifier and a hydrophilic modifier on the surface of nano-silicon dioxide. The hydrophilicity of the surface of nano-silicon dioxide is reduced as much as possible so that it can be dispersed in the oil phase; and a small part of the hydrophilic groups is retained so that it can react with a polymer compound containing a large number of hydrophilic groups to suspend the polymer compound. The coexistence of hydrophilic and hydrophobic groups on the surface of nano-silicon dioxide also avoids copolymerization caused by a single hydrophilic group and hydrophobic association caused by a single hydrophobic group, thereby increasing the dispersibility of nano-silicon dioxide.

[0033] Embodiment 11: In the first step, 30g of nano-silica prepared by hydrolysis precipitation method was added to a 250ml three-necked flask, 80g of cyclohexane was added, and ultrasonic dispersion was performed for 30min. In the second step, 20g of cyclohexane, 3g of trimethoxy (pentyl) silane and 1g of 1-amino-5-(trimethoxysilyl) pentane-2-ol were added to a 100ml beaker, and the mixture was sealed with a sealing film after mixing evenly, and magnetic stirring was performed at room temperature for 30min to obtain a modifier mixture. In the third step, the three-necked flask containing nano-silica was placed in a water bath, the water bath temperature was set to 50°C, the pH was adjusted to 4.5 to 5 with 1mol / L hydrochloric acid, and the modifier mixture was added dropwise to the three-necked flask. After the addition was completed, it was stirred for 10h, and then centrifuged, washed, placed in a 105°C oven for 7h, and ground to obtain nano-silica with controllable hydrophobicity.

[0034] Embodiment 12: In the first step, 50g of nano-silica prepared by hydrolysis precipitation method was added to a 250ml three-necked flask, 90g of cyclohexane was added, and ultrasonic dispersion was performed for 30min. In the second step, 30g of cyclohexane, 6g of trimethoxy (hexyl) silane and 1g of 1-amino-5-(trimethoxysilyl) pentane-2-ol were added to a 100ml beaker, and the mixture was sealed with a sealing film after mixing evenly, and magnetic stirring was performed at room temperature for 30min to obtain a modifier mixture. In the third step, the three-necked flask containing nano-silica was placed in a water bath, the water bath temperature was set to 60°C, the pH was adjusted to 4.5 to 5 with 1mol / L hydrochloric acid, and the modifier mixture was added dropwise to the three-necked flask. After the addition was completed, it was stirred for 15h, and then centrifuged, washed, placed in a 105°C oven to dry for 10h, and ground to obtain nano-silica with controllable hydrophobicity.

[0035] Embodiment 13: In the first step, 50g of nano-silica prepared by hydrolysis precipitation method was added to a 250ml three-necked flask, 80g of cyclohexane was added, and ultrasonic dispersion was performed for 30min. In the second step, 25g of cyclohexane, 4g of trimethoxy (hexyl) silane and 1g of 1-amino-6-(trimethoxysilyl) hexane-2-ol were added to a 100ml beaker, and the mixture was sealed with a sealing film after mixing evenly, and magnetic stirring was performed at room temperature for 30min to obtain a modifier mixture. In the third step, the three-necked flask containing nano-silica was placed in a water bath, the water bath temperature was set to 50°C, the pH was adjusted to 4.5 to 5 with 1mol / L hydrochloric acid, and the modifier mixture was added dropwise to the three-necked flask. After the addition was completed, it was stirred for 10h, and then centrifuged, washed, placed in a 105°C oven to dry for 10h, and ground to obtain nano-silica with controllable hydrophobicity.

[0036] Embodiment 14: In the first step, 40g of nano-silica prepared by hydrolysis precipitation method was added to a 250ml three-necked flask, 90g of cyclohexane was added, and ultrasonic dispersion was performed for 30min. In the second step, 25g of cyclohexane, 3g of trimethoxy (hexyl) silane and 1g of 1-amino-6-(trimethoxysilyl) hexane-2-ol were added to a 100ml beaker, and the mixture was sealed with a sealing film after mixing evenly, and magnetic stirring was performed at room temperature for 30min to obtain a modifier mixture. In the third step, the three-necked flask containing nano-silica was placed in a water bath, the water bath temperature was set to 40°C, the pH was adjusted to 4.5 to 5 with 1mol / L hydrochloric acid, and the modifier mixture was added dropwise to the three-necked flask, and stirred for 10h after the addition was completed, and then centrifuged, washed, placed in a 105°C oven to dry for 10h, and ground to obtain nano-silica with controllable hydrophobicity.

[0037] Embodiment 15: In the first step, 30g of nano-silica prepared by hydrolysis precipitation method was added to a 250ml three-necked flask, 80g of cyclohexane was added, and ultrasonic dispersion was performed for 30min. In the second step, 30g of cyclohexane, 5g of trimethoxy (pentyl) silane and 1g of 1-amino-6-(trimethoxysilyl) hexane-2-ol were added to a 100ml beaker, and the mixture was sealed with a sealing film after mixing evenly, and magnetic stirring was performed at room temperature for 30min to obtain a modifier mixture. In the third step, the three-necked flask containing nano-silica was placed in a water bath, the water bath temperature was set to 40°C, the pH was adjusted to 4.5 to 5 with 1mol / L hydrochloric acid, and the modifier mixture was added dropwise to the three-necked flask. After the addition was completed, it was stirred for 12h, and then centrifuged, washed, placed in a 105°C oven for 8h, and ground to obtain nano-silica with controllable hydrophobicity.

[0038] Comparative Example 1: Add 30g of nano-silica prepared by hydrolysis precipitation method to a 250ml three-necked flask, add 80g of cyclohexane, and ultrasonically disperse for 30min. Add 30g of cyclohexane to a 100ml beaker, add 6g of 3-methacryloxypropyltrimethoxysilane, mix well and seal with a sealing film, and stir magnetically for 30min at room temperature. Place the three-necked flask containing nano-silica in a water bath, set the water bath temperature to 40℃, adjust the pH to 4.5 to 5 with 1mol / L hydrochloric acid, drop the mixed modifier into the three-necked flask, stir for 12h after the addition, then centrifuge, wash, put in a 105℃ oven to dry for 8h, and grind to obtain modified nano-silica.

[0039] The performance test was performed on the hydrophobicity controllable nano-silica prepared in the above-mentioned Examples 11 to 15 and the modified nano-silica product prepared in Comparative Example 1. 6 g of each of the hydrophobicity controllable nano-silica prepared in Examples 11 to 15 and the modified nano-silica (particle size 40 nm) prepared in Comparative Example 1 were added to a container containing 44.g of white oil, and then 48 g of anionic polyacrylamide (molecular weight 6 million) and 1.2 g of surfactant were added respectively. After emulsification and ultrasonic treatment, they were placed in a 150 ml measuring cylinder to observe the stratification and precipitation. The sedimentation rate Sr (the percentage of the clear interface drop distance to the total height of the liquid surface) was introduced to test the suspension stability of 7d, and the test results are shown in Table 1. The test results in Table 1 show that the hydrophobicity controllable nano-silica of the present invention is more conducive to the stability of the system when applied to the suspended continuous mixing fracturing fluid system than the nano-silica modified with only 3-methacryloxypropyltrimethoxysilane, and the stability time is longer.

[0040] In summary, the present invention provides a nano-silica with controllable hydrophobicity and a preparation method thereof. By grafting a hydrophobic modifier and a hydrophilic modifier, the number of hydrophilic groups and hydrophobic groups on the surface of the nano-silica is quantitatively controlled. The hydrophilicity of the surface of the nano-silica is reduced as much as possible so that it can be dispersed in the oil phase; and a small portion of the hydrophilic groups is retained so that it can react with a polymer compound containing a large number of hydrophilic groups to suspend the polymer compound. The coexistence of hydrophilic and hydrophobic groups on the surface of the nano-silica also avoids copolymerization caused by a single hydrophilic group and hydrophobic association caused by a single hydrophobic group, thereby increasing the dispersibility of the nano-silica.

[0041] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A hydrophobicity controllable nano-silica, characterized in that Prepared according to the following steps: The first step is to add the required amount of nano-silicon dioxide and solvent into the first reactor and disperse them by ultrasonic; The second step is to add the required amount of solvent, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH to 4.5 to 5, add the modifier mixture to the first reactor, stir the reaction for 10 to 15 hours, and centrifuge, wash, dry and grind the reaction product to obtain nano-silica with controllable hydrophobicity.

2. The hydrophobicity controllable nano-silica according to claim 1, characterized in that The solvents in the first and second steps are both cyclohexane. In the first step, the mass ratio of nano-silica to cyclohexane is 3 to 5:8 to 9. In the second step, the mass ratio of the total mass of the hydrophobic modifier and the hydrophilic modifier to cyclohexane is 2 to 8:20 to 30.

3. The hydrophobicity controllable nano-silica according to claim 1 or 2, characterized in that The hydrophobic modifier is trimethoxy(pentyl)silane or trimethoxy(hexyl)silane.

4. The hydrophobicity-controllable nano-silica according to any one of claims 1 to 3, characterized in that The hydrophilic modifier is 1-amino-5-(trimethoxysilyl)pentan-2-ol or 1-amino-6-(trimethoxysilyl)hexan-2-ol.

5. The hydrophobicity-controllable nano-silica according to any one of claims 1 to 4, characterized in that The mass ratio of the hydrophobic modifier to the hydrophilic modifier is 3 to 6:

1.

6. The hydrophobicity-controllable nano-silica according to any one of claims 1 to 5, characterized in that The mass ratio of the hydrophobic modifier, the hydrophilic modifier and the nano-silica is 3 to 6:1:30 to 60.

7. The hydrophobicity-controllable nano-silica according to any one of claims 1 to 6, characterized in that In the third step, the particle size of the hydrophobicity-controllable nano-silica obtained after grinding is 30 nm to 50 nm.

8. The hydrophobicity-controllable nano-silica according to any one of claims 1 to 7, characterized in that In the first step, nano silicon dioxide is prepared by a hydrolysis precipitation method; or / and, in the third step, 1 mol / L hydrochloric acid is added to the first reactor at 40° C. to 60° C. to adjust the pH.

9. A method for preparing nano-silica with controllable hydrophobicity according to claims 1 to 8, characterized in that Follow these steps: The first step is to add the required amount of nano-silicon dioxide and solvent into the first reactor and disperse them by ultrasonic; The second step is to add the required amount of solvent, hydrophobic modifier and hydrophilic modifier into the second reactor, seal the second reactor, and stir at room temperature to obtain a modifier mixed solution; The third step is to add hydrochloric acid to the first reactor at the desired temperature to adjust the pH to 4.5 to 5, add the modifier mixture to the first reactor, stir the reaction for 10 to 15 hours, and centrifuge, wash, dry and grind the reaction product to obtain nano-silica with controllable hydrophobicity.

10. Use of the hydrophobicity controllable nano-silicon dioxide according to any one of claims 1 to 8 in fracturing fluid.

Citation Information

Patent Citations

  • Modified nano silicon dioxide, modification method thereof, anticorrosive coating and coating

    CN111040472A

  • Surface modification method of nano silicon dioxide

    CN113234335A